2013
DOI: 10.4103/0028-3886.125273
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent meningeal inflammatory myofibroblastic tumor: A case report and literature review

Abstract: An inflammatory myofibroblastic tumor (IMT) is a rare lesion with an uncertain prognosis and a disorder difficult to classify. IMTs are a heterogeneous group of lesions, sometimes indistinguishable from meningiomas and other expanding or inflammatory lesions of the central nervous system. This report presents a patient with IMT, who presented with recurrent retroocular pain radiating to the occipital region and no neurologic deficits. He had early recurrence in spite of total resection of the lesion. The clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Gallago et al studied all cases of recurrence in IMT-CNS and found 19 such instances in over 100 cases reviewed. 3 Going through their data, we noted that the PCG variants had higher chances of recurrence than the FHC variants, and 11 out of 19 (57.8%) patients were females. Twelve of the cases (63%) who showed recurrence had not undergone gross total resection as their primary modality of management.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Gallago et al studied all cases of recurrence in IMT-CNS and found 19 such instances in over 100 cases reviewed. 3 Going through their data, we noted that the PCG variants had higher chances of recurrence than the FHC variants, and 11 out of 19 (57.8%) patients were females. Twelve of the cases (63%) who showed recurrence had not undergone gross total resection as their primary modality of management.…”
Section: Discussionmentioning
confidence: 89%
“…2 IMT-CNS is a rare entity, with only 100 cases being reported so far. 3 Most tumors arise from meningeal structures, though intracerebral and intraventricular lesions have been known to occur. 4 From our literature search, only 7 cases of intrasellar IMT have been reported until now (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…While tumors with ALK gene rearrangements are readily considered a unique neoplastic category, histologically similar neoplastic lesions may lack this genetic alteration[ 6 ]. ALK expression is positive in nearly 50% of patients with IMT, especially in children, and is associated with local recurrence and distant metastasis[ 7 ]. However, in the literature we reviewed, only about 25% of cases were positive for ALK expression.…”
Section: Discussionmentioning
confidence: 99%
“…After incomplete resection, 40% recurrence rate is seen within 2 years. [ 8 9 ] Recurrence rate after gross total resection for ALK-positive and ALK-negative cases is around 33% and 9%, respectively. Most recurrences in ALK-positive patients occur within 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%